PENGARUH OVERCONFIDENCE BIAS, MENTAL ACCOUNTING DAN FAMILIARITY BIAS TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI - Amir Hamzah; Andi Supriadi; Dede Djuniardi (Journal of Global Business and Management Review, 2022)
This study aims to determine and analyze the effect of Overconfidence Bias, Mental Accounting and Familiarity Bias on investment decision making (case studies of victims of illegal binary option investments) either simultaneously or partially. The research method used was descriptive and verification methods. The research population is all victims of illegal Binary Options investment in Indonesia. The sampling technique used was the Probability Sampling Technique with the Simple Random Sampling method. Calculation of the sample in this study using the slovin formula. The data collection technique uses a questionnaire distributed to all victims of illegal Binary Options investment in Indonesia, while the data analysis technique uses multiple regression analysis. The results of the study show that Overconfidence Bias, Mental Accounting and Familiarity Bias simultaneously affect investment decision making. Overconfidence Bias, Mental Accounting and Familiarity Bias partially positive and significant effect on investment decision making.